(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aims to Measuring the auditors’ commitment with the analytical procedures of the economic units of the research sample in carrying out their professional duties and the importance of this commitment to the tax administration and the extent of their reliance on the external auditor’s report and the financial statements in determining the income tax and its effect on the tax revenues. The research depends on a main hypothesis stating that "The use of analytical procedures by the external auditor has a positive impact on the availability of confidence and credibility in the financial statements presented to the tax administration and has a positive impact on the tax revenues." The research has reached a number of conclusions. The most prominent of these are the following: The use of analytical procedures provides a set of indicators and ratios that are comparable with standard indicators and ratios and therefore the availability of analytical information based on scientific foundations rather than personal assessment. This leads to a reduction in the personal judgment of both the tax auditor and external auditor. The research has concluded with a set of recommendations which included: - Activating analytical procedures as a means of modernizing the process of auditing and expanding them in order to reach the accuracy of the results and their reality. Also showing the importance of financial analysis and its direct link to the application of analytical procedures and its adoption as an important tool in tax settlement because it is based on scientific foundations to contribute in tax payer’s satisfaction with the amount of tax imposed on him on the one hand and the achievement of fair tax revenues on the other hand.